IMPLEMENTASI PEMANFAATAN SAMPAH KULIT KERANG DAN GONGGONG DI DESA KAMPUNG TUA BAKAU SERIP - Frangky Silitonga; Arina Luthfini Lubis; Agung Arif Gunawan; Thania Nadhirah Amalina; Joshua Cesario Matulessy (PUAN INDONESIA, 2026)
of the real efforts in supporting environmental management while improving community welfare. Through socialization and training activities facilitated by the Pandang Tak Jemu Tourism Awareness Group (Pokdarwis), the community was taught how to process shells and bark waste into handicraft products with selling value. This program includes the introduction of simple technology in the form of a shell-cutting machine, material processing techniques to become ready-to-use products, as well as digital-based marketing strategies through social media and village websites. The results of the training not only encourage community creativity in producing distinctive local products, but also open up new business opportunities based on the potential of previously wasted resources. Thus, the implementation of this program contributes to waste reduction, skill building, job creation, and supports the sustainable development of tourist villages in the Shire Mangrove. The success of this program shows that waste utilization can be optimized into creative economic innovations that have a positive impact on the environment, social, and economic of the local community.